AN ANALYSIS OF TEACHING EAP TO LAW STUDENTS AT LAW FACULTY OF MUHAMMADIYAH UNIVERSITY OF SURAKARTA IN 2006/2007 ACADEMIC YEAR - WIJAYANTI , TITUT (2007)
This research paper is conducted to know how is the implementation of teaching EAP to Law students and to know what are the difficulties of teaching and learning EAP. The researcher uses descriptive qualitative method. The researcher collects dat by observing the EAP class and conducting interviews with the lecturer of EAP and the students. The respondents are the students and lecturer of EAP class at Law Faculty of Muhammadiyah University of Surakarta in 2006/2007 academic year.The lecturer uses Grammar Translation Method in presenting the material besides, she uses ESA technique for classroom presentation. In carrying out the test, she only uses the post-test. It is given in the last meeting. By conducting the test, the lecturer can measure the students' achievement. The result of the data analysis. First, about the implementation of teaching EAP consists of goal of teaching EAP, EAP syllabus, procedure activities, namely;lecturer's role, students' role, classroom activities, and evaluation. Second, about the difficulties of teaching and learning EAP. In teaching EAP lecturer has five difficulties and in learning EAP students have eight difficulties.